ZooNom: an online thesaurus for alleviating ambiguity in the terminology of zoological nomenclature - Saliba, Elie Mario; Vignes-Lebbe, Régine; Dubois, Alain; Ohler, Annemarie (Zootaxa, 2021)
Zoological nomenclature is the discipline of taxonomy responsible for regulating the scientific names of animal species. It has its roots in Carolus Linnaeusʼ work and has been governed by an international Code since the turn of the 20th century. Its vocabulary, on the other hand, is not always clear. Various authors have established new terminology in order to reduce ambiguity. To make these new terms, but also the classical terms used by the International Code of Zoological Nomenclature, accessible, an electronic thesaurus (link: https://www.loterre.fr/skosmos/FM8/en/) was created, allowing to compare existing terminologies. This thesaurus is also a tool for reflection and discussion, targeting taxonomists and experts in nomenclature.